About the Journal - Jegels, Llewellin RG (WritingThreeSixty: Journal or Research and Creative Text, 2021)
WritingThreeSixty is a bi-annual, interdisciplinary journal for research essays and creative works. First launched in 2014 as an initiative of the English department at the University of the Western Cape (UWC), WritingThreeSixty now forms part of the broader community within the Arts Faculty and Humanities at UWC. This journal maintains the standard of peer review and wishes to provide a platform to develop a culture of publishing among postgraduate and emerging students, as well as established creative artists within UWC and South Africa at large.WritingThreeSixty also forms part of co-curricular graduate culture at UWC that affords students the opportunity to develop professional skills through the voluntary leadership and service positions created through the journal. These positions include the management of the journal and its team, editorial outputs, as well as our digital marketing efforts that are presented through social media and our online website.